Enhancing Nutritional Education Through the Development of Toddler Biscuits: A Focus on Mung Bean Flour and Patin Fish Paste as Effective Nutritional Interventions Against Malnutrition - Sajiman Sajiman; Zulfiana Dewi (Postgraduate, University of Mataram, 2026)
This study aims to formulate toddler biscuits from mung bean flour and patin fish paste and to analyze their sensory quality, proximate content, amino acid profile, and fatty acid profile. Biscuits were prepared with varying ratios of mung bean flour and patin fish paste (10:90 to 90:10). Sensory quality tests were conducted using a hedonic scale scoring method with 30 trained panelists. The best formulation was selected using the De-Garmo test. Proximate analysis, amino acid profile, and fatty acid profile were performed on the best formulation and compared with standard toddler PMT biscuits. The KHIP5050 formulation (50% mung bean flour: 50% patin fish paste) was determined to be the best treatment based on the highest total De-Garmo score (3.33). Nutritionally, KHIP5050 biscuits had higher energy (479.45 kcal), protein (16.81%), and fat (27.77%) compared to standard PMT biscuits. The fatty acid profile was superior, with higher levels of MUFA and PUFA, and the presence of EPA, DHA, and AA, which were not detected in the standard biscuits. Toddler biscuits based on mung bean flour and patin fish paste, especially the KHIP5050 formulation, have significant potential as a nutrient-dense food product to address malnutrition in toddlers.